A performance analysis of national programme for community empowerment in rural Indonesia - Ida Zulfida; Ahmad Fauzi (Proceedings of AICS - Social Sciences, 2017)
Rural empowerment programs have been widely used in Indonesia as a means to accelerate rural development from the human capital perspective. One such rural empowerment program is the Program Nasional Pemberdayaan Masyarakat Perdesaan (PNPM) [National Program for Community Empowerment]. As much as Rp 64.87 trillion (US 4.8 billion) has been spent delivering this program across the country. Nevertheless, very few assessments have been conducted to assess the effectiveness of this national program. This study attempts to evaluate the program in Bandung Regency in Indonesia. Using data envelopment analysis (DEA), this study explores the effectiveness of the empowerment program by measuring its inputs and outputs. Using data from sub districts and villages, the low efficiency score of the program reveals inefficiencies of input and misallocation of budget. This paper also describes some lessons learned for rural development program in Indonesia.